Pengaruh Jumlah Usaha Mikro Kecil Dan Menengah (UMKM), Jumlah Tenaga Kerja UMKM Dan Penanaman Modal Dalam Negeri (PMDN) Terhadap Pertumbuhan Ekonomi di Indonesia - Juliansyah, Hijri; Tursina, Tursina; Zubair, Ahmad (Jurnal Ekonomi Regional Unimal, 2024)
This study aims to analyze the influence of the number of micro, small, and medium enterprises (MSMEs), workers in micro, small, and medium enterprises (MSMEs), and domestic investment (PMDN) on Indonesia's economic growth, both in the short and long term. The data used in this study are secondary time series data from 1993 to 2023, obtained from the Central Bureau of Statistics (BPS) and the World Bank. The analysis was conducted using the Autoregressive Distributed Lag (ARDL) model. The result showed that in the short run the number of micro, small, and medium enterprises (MSMeS), worker MSMeS, and domestic investment is positive and significantly effect economy growth of indonesia in the long run the number of micro, small and medium (MSMes), worker MSMeS, and domestic investment are also positive and significantly effect economy growth of indonesia.